EU-approved rapid tests might underestimate bovine spongiform encephalopathy infection in goats. (March 2017) - Meloni, Daniela; Bozzetta, Elena; Langeveld, Jan P. M.; Groschup, Martin H.; Goldmann, Wilfred; Andrèoletti, Olivier; Lantier, Isabelle; Van Keulen, Lucien; Bossers, Alex; Pitardi, Danilo; Nonno, Romolo; Sklaviadis, Theodoros; et al.
We report the diagnostic sensitivity of 3 EU-approved rapid tests (ELISAs; 1 from IDEXX and 2 from Bio-Rad) for the detection of transmissible spongiform encephalopathy diseases in goats. Ninety-eight goat brainstem samples were tested. All the rapid tests had 100% specificity and ≥80% sensitivity, with the IDEXX test significantly more sensitive than the 2 Bio-Rad tests. All tests detected 100% of samples from goats with clinical scrapie, but missed 8% (IDEXX) to 33% (Bio-Rad SG) of samples from preclinical goats. Importantly, only IDEXX picked up all samples from clinical bovine spongiform encephalopathy (BSE)-infected goats, whereas the other 2 rapid tests missed 15% (Bio-Rad SG) to 25% (Bio-Rad SAP). These results show that a fraction of preclinical scrapie infections are likely missed by EU surveillance, with sensitivity of detection strongly dependent on the choice of the rapid test. Moreover, a significant proportion of clinical BSE infections are underestimated by using either Bio-Rad test. Assuming that the same sensitivity on preclinical goats would also occur in BSE-infected goats, our data suggest that IDEXX is likely the most sensitive test for detecting preclinical field cases of BSE infection in goats, although with an 8% failure rate. These results raise some concerns about the reliability of current EU surveillance figures on BSE infection in goats.